2021
DOI: 10.3389/fmolb.2021.637550
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Spike Surface Glycoprotein in Severe Acute Respiratory Syndrome–Coronavirus

Abstract: The novel coronavirus originated in December 2019 in Hubei, China. This contagious disease named as COVID-19 resulted in a massive expansion within 6 months by spreading to more than 213 countries. Despite the availability of antiviral drugs for the treatment of various viral infections, it was concluded by the WHO that there is no medicine to treat novel CoV, SARS-CoV-2. It has been confirmed that SARS-COV-2 is the most highly virulent human coronavirus and occupies the third position following SARS and MERS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 115 publications
(147 reference statements)
0
7
0
Order By: Relevance
“…Currently, a large number of studies have reported that the interaction between RBD located at the spike protein of SARS-CoV-2 and the receptor ACE2 on host cells is essential for viral entry [ 26 , 27 ]. Moreover, antibodies against RBD at the recovery phase of COVID-19 present neutralizing activity because they can block the interaction between ACE2 and viral spike protein [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, a large number of studies have reported that the interaction between RBD located at the spike protein of SARS-CoV-2 and the receptor ACE2 on host cells is essential for viral entry [ 26 , 27 ]. Moreover, antibodies against RBD at the recovery phase of COVID-19 present neutralizing activity because they can block the interaction between ACE2 and viral spike protein [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“… 106 Coronaviruses consist of four main structural proteins, with the membrane (M), envelope (E), and nucleocapsid (N) proteins in addition to the S-protein of focus in the present paper. 107 …”
Section: Evolution Of the S-protein In A Structural Contextmentioning
confidence: 99%
“…SARS-CoV-2 is the seventh coronavirus known to infect Homo sapiens , the others being the common-cold causing HCoV-229E, HCoV-NL63, HCoV-HKU1, and HCoV-OC43, as well as the more pathogenic SARS-CoV-1 and MERS-CoV. , While some of the milder of these are α-coronaviruses and some β-coronaviruses (OC43, HKU1), all the three most pathogenic viruses are β-coronaviruses with distinct functional properties . Coronaviruses consist of four main structural proteins, with the membrane (M), envelope (E), and nucleocapsid (N) proteins in addition to the S-protein of focus in the present paper …”
Section: Evolution Of the S-protein In A Structural Contextmentioning
confidence: 99%
See 2 more Smart Citations